1981
DOI: 10.1111/j.1476-5381.1981.tb10447.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo PHARMACOLOGICAL STUDIES ON THE INTERACTIONS BETWEEN TRYPTAMINE AND 5‐HYDROXYTRYPTAMINE

Abstract: 1 Three methods have been used in an attempt to study the interactions of tryptamine with central 5-hydroxytryptamine (5-HT) systems. 2 In groups of mice pretreated with tranylcypromine, tryptamine reduced the number of mice showing head twitches following the 5-HT precursor, 5-hydroxytryptophan. This effect was not seen in mice pretreated with saline and tryptamine itself did not induce head twitches in either group. 3 The swallowing reflex induced by 5-hydroxytryptophan in rats anaesthetized with urethane wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has been speculated that tryptamine might be a neuromodulator, perhaps opposing the actions of serotonin (5-hydroxytryptamine; 5-HT) and, thus, playing a role in the regulation of mood, emotion, sleep, and appetite (Jones, 1981(Jones, , 1982, the cardinal functions of 5-HT. Elevated tryptamine urinary excretion has been observed in schizophrenic patients, attributed to low MAO activity (Sullivan et al, 1980).…”
mentioning
confidence: 99%
“…It has been speculated that tryptamine might be a neuromodulator, perhaps opposing the actions of serotonin (5-hydroxytryptamine; 5-HT) and, thus, playing a role in the regulation of mood, emotion, sleep, and appetite (Jones, 1981(Jones, , 1982, the cardinal functions of 5-HT. Elevated tryptamine urinary excretion has been observed in schizophrenic patients, attributed to low MAO activity (Sullivan et al, 1980).…”
mentioning
confidence: 99%
“…It seemed possible that these responses were mediated by two different receptor populations within the preoptic anterior hypothalamus since they had different susceptibilities to blockade by indoleamine-receptor antagonists (Cox, Lee & Martin, 1981). Recently, results from behavioural (Jones, 1981) and ionophoretic studies (Jones & Boulton, 1980) have suggested that tryptamine may modulate central 5-HT activity. Therefore, it was of interest to attempt to determine whether 5-HT and tryptamine acted in the same or separate pathways to produce their respective changes in core temperature.…”
mentioning
confidence: 99%